Madras Education In Turkey In The MidXIX And Early XX Century - Abdurahim Khasanovich Khasanov (Global Scientific Publishing, 2022)
The history of madrasa education in Turkestan, the educational process, the teachers who taught in madrasas, their potential, their level, teaching methods, professions and positions occupied by students, the conditions created for studying in madrasas, what books and subjects were taught, the teachers capacity, information about the rules of the internal procedure is given.
Keywords: Madrasah; hujra; Shaykhulislam; mudarris